MANAJAMEN ISTIBDAL ATAS ASET WAKAF SEBAGAI PEMBANGUNAN EKONOMI - Arifin, Nur Rachmat; Muhtadi, Ridan; Aziz, Abd (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2020)
Abstract This paper is to formulate a model through which Istibdal management can increase waqf assets more productively and as economic development. This model is built on the basis of understanding the concept of waqf, learning from past and present waqf institutions and addressing the issue of waqf in Indonesia. This research uses descriptive qualitative research with the library research method. This study uses secondary data from the Indonesian Waqf Board (BWI), books, journals, bulletins, government reports and websites. The whole process can be managed by a waqf institution as a waqf nazdir which collaborates to be supervised by BWI (Indonesian Waqf Agency) in using waqf assets in accordance with syaraih principles and as economic development. This research shows how Istibdal management can assist the Government of Indonesia in economic development with mixed public goods and public goods. This implies an alternative source of funding for Development. The application of the concept of waqf can learn and adapt from the model developed in this paper. This paper attempts to revive the function of waqf as a provider of diverse public goods and public goods from Islamic history. Incidentally, this paper also introduces waqf as economic development in Indonesia. Abstrak Paper ini adalah untuk merumuskan model melalui manajamen Istibdal dapat meningkatkan aset wakaf lebih produktif dan sebagai pembangunan ekonomi. Model ini dibangun atas dasar pemahaman konsep wakaf, belajar dari lembaga wakaf dari masa lalu dan sekarang dan menangani masalah perwakafan di Indonesia. Penelitian ini menggunakan penelitian kualitatif deskriptif dengan metode kepustakaan atau library research. Penelitian ini menggunakan data sekunder berasal dari Badan Wakaf Indoneisa (BWI), buku, Jurnal, buletin, laporan pemerintah dan website. Proses keseluruhan dapatdikelola oleh lembaga wakaf sebagai nazdir wakaf yang bekerjasama diawasi BWI (Badan Wakaf Indonesia) dalam menggunakan harta wakaf sesuai dengan kaidah syaraih dan sebagai pembangunan ekonomi. Penelitian ini menunjukkan bagaimana manajamen Istibdal dapat membantu Pemerintah Indonesia dalam pembangunan ekonomi dengan barang publik dan barang publik campuran. Ini secara tidak langsung menunjukkan alternatif sumber pendanaan untuk Pembangunan. Penerapan konsep wakaf dapat belajar dan beradaptasi dari model yang dikembangkan dalam paper ini. Tulisan ini mencoba untuk menghidupkan kembali fungsi wakaf sebagai penyedia barang publik dan barang publik yang beragam dari sejarah Islam. Secara tidak sengaja, makalah ini juga memperkenalkan wakaf sebagai pembangunan ekonomi di Indonesia.